Lyginamosios konstrukcijos 1647 m. Ewangelie polskie y litewskie vertime - Judžentis, Artūras; Lučinskienė, Milda (Baltistica, 2008)
Comparative constructions in the translation of Ewangelie polskie y litewskie (1647) The article deals with the comparative constructions in Ewangelie polskie y litewskie (1647), a book used for Gospel readings during Catholic mass. Attention is focused on the syntactic structure of these constructions and on the semantic relations that they express. The Gospels translated by Jaknavičius (it is thought that he translated a large majority of them) were carefully compared with the remaining translations thought to be done an anonymous translator, and both were compared with the originals. The conclusions are layed out as follows: 1. The main types of the modifying comparative constructions in the Gospels, translated by Jaknavičius, are those introduced by the subordinator kaip. The comparative standard of these constructions usually follows the criterion; a few cases of the opposite order of constituents correspond to the original. 2. The standard preposing is characteristic of the comparative constructions with correlative subordinators. This order of constituents does not always correspond to that of the Polish original; however, this discrepancy can probably be related to unique aspects particular to Lithuanian. 3. Comparative constructions with the negative standard of comparison and similar contrastive constructions with the subordinator jeigi… kaip and additive (copulative) constructions with the subordinator kaip(o)… ir are considered to be syntactic loan-translations. 4. Comparative constructions with the phrase kaip būtų functioning as a subordinator and active participles are used by Jaknavičius to express non-evidential modality. 5. The construction with the correlative conjunction kuo... tuo is used in Jaknavičius’ translation to denote the emphasis of comparison between two similar structures. 6. The comparison of the constructions with the genitive of the pronoun kiekas in the function of a subordinator, and the constructions, introduced by the adverb kiek, leads to the presumption that adverbialisation of the pronoun kiekas, *kieka was gradual and depended on semantic relations with other constituents in the proposition and on the syntactic position in the sentence: the verb-independent pronouns made the adverbialisation process quicker than the verb-governed ones. 7. No constructions of comparative cases were found in the Gospels, nevertheless some traces of them can be found in Jaknavičius’ translation. 8. Comparative constructions with prepositions in Jaknavičius’ translation are presuppositional or exclusive. These constructions correspond to case constructions, and sometimes – to prepositional constructions in Latin and Greek originals. The standard of comparison in these constructions always follows the criterion. 9. Complex sentences with the conjunction neg (full form negi) constitute the main type of Jaknavičius’ comparative constructions denoting inequality. Constructions with the conjunction neig are only seldom used in the translation. 10. The standard of comparison always follows the criterion in comparative constructions of inequality. The order of constituents in the constructions corresponds to that of the original in all cases, nevertheless there is no sufficient evidence to regard this order as being conditioned by the Polish language. 11. Comparative clauses with the full-form subordinator kaipo are characteristic of the last seven Gospels translated by the anonymous translator. These clauses, as well as the ones, translated by Jaknavičius, have greatly been influenced by the syntactic structure of the original. Besides the facts mentioned above, there are some minor differences in the use of subordinators in Jaknavičius’ translations and in the translation by the anonymous translator.